Design and Fabrication of Vehicle All-Wheel-Nuts Remover - ABDULLAH, Mohd Azman; Sulaiman, Nurfarahin; Mat Idera, Ikhwan Hakim; Mohd Razi, Mohd Zakwan; Ngadiman, Mad Nasir (2013)
As the standard of living in Malaysia has increased, most of the families have at least one vehicle, typically, car, to move easily and quickly. With the increment of the number of cars in the road, the number of cars’ problem due to tyre failure has increased. Often, the car is provided with tyre wheel nuts remover and jack for instance spare tyre replacement. Nevertheless, due to the difficulty in applying the required torque to remove the nuts, most of the time, driver rely on the tow truck and available nearest mechanic to solve the problem. This always happen to the elderly or female drivers. Based on the capability of torque application by these drivers, a vehicle all-wheel-nuts remover is designed. The remover is designed to be ergonomic to be used, easy maintenance, easy storage, easy to handle and able to remove all nuts at once. The design of the remover is based on standard pitch circle diameter (PCD) of 100 mm and 4 numbers of nuts for most of the cars available.